Treatment of hypophosphataemic vitamin D-resistant rickets with massive doses of 1 alpha-hydroxy-vitamin D3 during childhood. Issue 1 (January 1980) - Seino, Y; Shimotsuji, T; Ishii, T; Ishida, M; Ikehara, C; Yamaoka, K; Yabuuchi, H; Dokoh, S
Abstract : Plasma levels of 1, 25 dihydroxy-vitamin D (1, 25-(OH)2-D) were low in 3 children with hypophosphataemic vitamin D-resistant rickets (HVDRR) during childhood, but increased after very large doses (0.5 to 2 micrograms/kg per day) of 1 alpha-hydroxy-vitamin D (1 alpha-OH-D3). This treatment has two advantages. Firstly, hypercalcaemia is easily controlled by reducing the dose of 1 alpha-OH-D3 because of its short half-life. Secondly, the administration of 1 alpha-OH-D3 to patients with HVDRR can enhance the tubular reabsorption of phosphate, and this seems desirable in treating HVDRR.